Long‐term warming effects on the microbiome and nifH gene abundance of a common moss species in sub‐Arctic tundra. Issue 6 (18th November 2021) - Klarenberg, Ingeborg J.; Keuschnig, Christoph; Russi Colmenares, Ana J.; Warshan, Denis; Jungblut, Anne D.; Jónsdóttir, Ingibjörg S.; Vilhelmsson, Oddur
Summary: Bacterial communities form the basis of biogeochemical processes and determine plant growth and health. Mosses harbour diverse bacterial communities that are involved in nitrogen fixation and carbon cycling. Global climate change is causing changes in aboveground plant biomass and shifting species composition in the Arctic, but little is known about the response of moss microbiomes in these environments. Here, we studied the total and potentially active bacterial communities associated with Racomitrium lanuginosum in response to a 20‐yr in situ warming in an Icelandic heathland. We evaluated the effect of warming and warming‐induced shrub expansion on the moss bacterial community composition and diversity, and nifH gene abundance. Warming changed both the total and the potentially active bacterial community structure, while litter abundance only affected the total bacterial community structure. The abundance of nifH genes was negatively affected by litter abundance. We also found shifts in the potentially nitrogen‐fixing community, with Nostoc decreasing and noncyanobacterial diazotrophs increasing in relative abundance. Our data suggest that the moss microbial community and potentially nitrogen fixing taxa will be sensitive to future warming, partly via changes in litter and shrub abundance.